2011
DOI: 10.1007/s10459-011-9306-3
|View full text |Cite
|
Sign up to set email alerts
|

Critically ill patients and end-of-life decision-making: the senior medical resident experience

Abstract: In order to improve the understanding of educational needs among residents caring for the critically ill, narrative accounts of 19 senior physician trainees participating in level of care decision-making were analyzed. In this multicentre qualitative study involving 9 university centers in Canada, in-depth interviews were conducted in either English or French, and the transcripts then underwent a hermeneutic phenomenological analysis. The resident was the central figure in the narrated incident, along with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 34 publications
(30 reference statements)
1
50
0
2
Order By: Relevance
“…Residents may also approach goals of care conversations in a scripted manner, with elements of the discussion and decision often misunderstood, and discrepancies between patients’ actual wishes and those documented [17, 18]. Residents perceive these conversations as difficult, often lack confidence in their own communication skills, and experience emotional distress [19, 20]. Assessment of residents’ perceptions and skills in having goals of care conversations will be important to verify or challenge program director perceptions within our local context.…”
Section: Discussionmentioning
confidence: 99%
“…Residents may also approach goals of care conversations in a scripted manner, with elements of the discussion and decision often misunderstood, and discrepancies between patients’ actual wishes and those documented [17, 18]. Residents perceive these conversations as difficult, often lack confidence in their own communication skills, and experience emotional distress [19, 20]. Assessment of residents’ perceptions and skills in having goals of care conversations will be important to verify or challenge program director perceptions within our local context.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of the residents in their study reported they received little to no faculty feedback on communication, whereas faculty felt they provided feedback. Studies from other medical disciplines report that residents felt that they would benefit from more education regarding communication, specifically breaking bad news, and feedback regarding communication skills [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Comme le mentionnent Good et DelVecchioGood, le détachement fait parti des apprentissages des futurs médecins et les craintes notées en l'occurrence sont probablement celles de novices [21] . En revanche, les émotions font parties du processus décisionnel et, comme elles sont hautement imprévisibles, il pourrait s'avérerfortutiled'apprendreauxétudiantsenmédecine à les gérer, et ce tout au long de leur formation médi-cale [22,23] .…”
Section: Discussionunclassified
“…C'est donc la souffrance projetée des participants qui pèse énormément dans leur processus décisionnel. On sait par ailleurs que cet aspect de la communication est rarement abordé en cours de formation [23,24] . De fait, les participants jugent leur formation en matière de DC actuellement insuffisante et se sentent mal outillés pour y faire face dans la pratique.…”
Section: Discussionunclassified